Glycemic status of diabetic patients attending in a diabetic hospital (TAJ: Journal of Teachers Association, 2018)
Diabetes care is now available everywhere in our country. But achievement of optimal level glycemic control and adherence to diabetic therapy is still questionable. This observational cross sectional study was done to observe the glycemic status of diabetic patients .The mean (±SD) serum HbA1c concentration of total subjects (n=100) was 7.84±2.0 with a range of 4.8-15.1%. The mean serum HbA1c concentration in group-1 subjects was 5.9±0.587% with a range of 4.8-6.9%, in group-2 subjects was 7.44±0. 304% with a range of 7.0-7.9%, in group-3 subjects was 9.55±1.52% with a range of 8.1-15.1%. Statistically significant difference (p=.001) was observed on serum HbA1c values in between the groups of subjects. Glycemic control was not satisfactory of these diabetic patients. Awareness and motivation through counseling and identifying certain factors influencing glycemic control might be able to overcome this situation.TAJ 2014; 27(2): 33-35